THE INFLUENCE OF WORK ENVIRONMENT, DELEGATION OF AUTHORITY AND BONUSES ON JOB SATISFACTION OF BATAM BRANCH EMPLOYMENT BPJS EMPLOYEES - Suyatni; Isnin; Rika Aprianti Ningsi; Rika Hardiantini; Zulfan; Nurhadiyanti (ZILLZELL MEDIA PRIMA, 2023)
This study supposed to obtain information about the relationship between the independent variables, namely; work environment (X1), delegation of authority (X2), and employee bonuses (X3) with the dependent variable, namely employee job satisfaction (Y) BPJS Ketenagakerjaan Batam Branch, either individually or together. The population and sample of this study were all employees of BPJS Ketenagakerjaan Batam Branch, totaling 35 people. By using the Slovin formula, a sample of 32 people was obtained. The results showed that there is a significant positive effect of work environment (X1), delegation of authority (X2), and bonuses (X3) on employee job satisfaction (Y) as indicated by the Fcount value of 23.247. This value is much smaller than the Fcount value at the 0.05 alpha significance level which is 2.95, or F = 23.247 < F0.05 (3:28) = 2.95. The relationship pattern of the four variables expressed by the multiple regression equation = -6.812 + 0.469X1 + 0.547X2 + 0.278X3. The variable that has the most influence is the delegation of authority variable, which has a coefficient of determination of 52.8%. This means that delegation of authority is the factor that most affects employee job satisfaction.